The Electrochemical and Spectroscopic Studies of trans-[LCo((DO)(DOH)pn)L'] Complexes - Ali Reza Rezvani; Hassan Hadadzadeh (Iranian Journal of Chemistry & Chemical Engineering, 2002)
Six new complexes of the type trans-[LCo((DO)(DOH)pn)L'] where (DO)(DOH)pn= N2, N2'-propanediolbis (2,3-butanedione 2-imine 3-oxime), L-Cl¯ and L'=mono-anaion of phenylcyanamide (pcyd), 2,5-dichlorophenylcyanamide (2,5-Cl2 pcyd), 2,4-dimethyl pehylcyanamide (2,4-Me2 pcyd) and L=L'=pcyd, 2,5-Cl2 pcyd, 2,4-Me2 pcyd, have been synthesized and characterized by elemental analysis, spectroscopy and cyclic voltammetry. The electronic absorption spectra of the Co(III) complexes show two low-energy ligand to metal charge transfer band that are associated with Co(III)-NCN chromophore. The cyclic voltammogrm of these complexes exhibit two subsequent quasi-reversible reduction couple repated to Co(III)/Co(II)  and Co(II)/Co(I), respectively.